Application of Quality Function Deployment Technique for Design and Development of Bamboo Furniture Sofa Set Product - Rawangwong, Surasit; Homkhiew, Chatree; Rodjananugoon, Julaluk; Boonyaso, Thipsukon (RMUTL Engineering Journal, 2022)
This research studies the design and development of bamboo furniture in the type of sofa set. The objective is to design and improve the quality of bamboo furniture products and compare customer satisfaction with traditional products by applying quality function deployment technique. The methodology starts with converting customer needs into the first matrix of quality function deployment technique, namely the product planning matrix or quality house, including quality house analysis results. It was found that the new product was designed and developed to meet the requirements of style, color, size, and weight. The material part is the production material durability of structural materials and durability of the jigs also in terms of convenience is the ease of use and movement of the product, and in terms of quality is the service life and the quality of the assembly. Finally, in terms of the price of the product. Then, the product satisfaction was compared between the old product and the new product. The results of this study revealed the new products showed higher satisfaction values ​​than the traditional products in all characteristics. The mean overall satisfaction of the new product was 4.11 points and the mean overall satisfaction of the old product was 3.36 points, representing a percentage change in the product of 22.32 percent.